P228 Recording of spirometry amongst patients with idiopathic pulmonary fibrosis in primary care: a UK general population based study. (December 2018) - Heyes, N; Hutchinson, JP; McKeever, T; Hubbard, RB; Navaratnam, V
Abstract : Background: We have previously shown that the incidence of idiopathic pulmonary fibrosis (IPF) in the UK is on the rise and that some individuals with IPF may be symptomatic up to five years prior to diagnosis. The aim of our study was to investigate recording of spirometry, in particular Forced Vital Capacity (FVC) amongst incident cases of IPF in primary care. Methods: Using data from The Health Improvement Network (THIN), an electronic longitudinal UK primary care database, we ascertained what proportion of incident cases of IPF had at least one recorded FVC prior to diagnosis. We used previously published Read Codes to identify incident cases of IPF and extracted information on FVC recorded prior to date of diagnosis. Logistic regression was used to generate odds ratios for the probability of having at least one recorded FVC amongst incident cases of IPF stratified by age, sex and calendar period of diagnosis. Results: Our cohort consisted of 2070 incident cases of IPF, of which 1305 (63.0%) were male and the mean age at diagnosis was 74.6 years (Standard Deviation [SD] 9.6). 488 cases (23.6%) had at least one FVC recorded prior to date of diagnosis. There was no association between gender and a record of FVC, after adjusting for age and calendar period of diagnosis. (Odds Ratio [OR] 0.97, 95% Confidence Interval [CI] 0.76 to 1.23). We also found that people with IPF over the age of 85 years were 63% less likely to have a recorded FVC compared to individuals with IPF under the age of 65 (OR 0.37, 95% CI 0.24 to 0.58) and individuals diagnosed from 2010 onwards were almost 19 times more likely to have a recorded FVC compared to individuals diagnosed prior to 2005 (OR 18.99, 95% CI 13.07 to 27.58). Conclusion: At present, spirometry amongst patients with IPF in primary care is poorly recorded, especially in the elderly.